Gobernanza, desarrollo y seguridad: trilemas e implicaciones para la coherencia de políticas - Madrueño-Aguilar, R. (Revista Iberoamericana de Estudios de Desarrollo)
This article analyzes the limits of global governance and policy coherence for development (CPD), based on the inescapable trilemmas of the global economy and the CPD approach. The analysis considers some of the main contradictions and institutional and political dilemmas that impact the system of international relations and the dynamics of development in an increasingly interdependent and complex world. The article adopts a macro-institutional approach with a historical and multilevel perspective, in order to highlight the political economy of contemporary development and the obstacles to the promotion of a global governance agenda for a sustainable development.